Enhancing Financial Resilience in Islamic Boarding Schools: An Operational Strategy Approach to Budget Deficit Reduction - Selvi Melianti; Amalia Irfani; Fitri Susanti Ilyas (Institut Agama Islam Negeri Pontianak, 2025)
This study aims to analyze how operational strategies are implemented to enhance financial resilience through budget deficit reduction in Islamic boarding schools. A qualitative approach with a case study design was employed, with data collected through observation, in-depth interviews, and documentation. Data were analyzed using data reduction, data display, and conclusion drawing techniques, while validity was ensured through source triangulation. The findings indicate that effective operational strategies include optimizing revenue sources, strengthening collaboration with village governments and external partners, improving expenditure efficiency, and conducting regular financial evaluations. These strategies have proven effective in maintaining operational stability despite challenges such as limited external support and fluctuations in student enrollment. However, this study is limited by its single-case design, which restricts the generalizability of the findings. The implications of this research highlight the importance of integrating planning, implementation, and control within operational management to support the sustainability of Islamic educational institutions. Practically, the findings offer valuable insights for administrators of Islamic boarding schools and similar institutions in designing adaptive and sustainable financial management strategies. The originality of this study lies in extending the operations management perspective within the context of Islamic education, particularly in strengthening financial resilience through a structured strategic approach.